2021
DOI: 10.3899/jrheum.210288
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Rheumatology Association Recommendation for the Use of COVID-19 Vaccination for Patients With Autoimmune Rheumatic Diseases

Abstract: Objective To develop guidance on the use of COVID-19 vaccines in patients with autoimmune rheumatic diseases (ARD). Methods The Canadian Rheumatology Association (CRA) formed a multidisciplinary panel including rheumatologists, researchers, methodologists, vaccine experts and patients. The panel used the GRADE approach. Outcomes were prioritized according to their importance for patients and clinicians. Evidence from the COVID-19 clinical trials was summarized. Indirect evidence for non-COVID-19 vaccines in AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
18
0
4
Order By: Relevance
“…Studies have shown that the current COVID-19 vaccines are effective and safe in adults [ 3 , 4 , 5 , 6 ]. Several international organizations and countries have also developed guidelines for different aspects of COVID-19 vaccination, including vaccination of special populations, management of adverse reactions, and cautions for vaccination [ 7 , 8 , 9 ]. However, the efficacy of protection and adverse effects of COVID-19 vaccines in children and adolescents remains unclear despite a large number of clinical trials being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the current COVID-19 vaccines are effective and safe in adults [ 3 , 4 , 5 , 6 ]. Several international organizations and countries have also developed guidelines for different aspects of COVID-19 vaccination, including vaccination of special populations, management of adverse reactions, and cautions for vaccination [ 7 , 8 , 9 ]. However, the efficacy of protection and adverse effects of COVID-19 vaccines in children and adolescents remains unclear despite a large number of clinical trials being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…В целом отсутствие синтеза нейтрализующих антител имело место у каждого 10-го пациента (9,5%), o n l i n e fi r s t Таблица 3. Рекомендации по терапии и вакцинации пациентов с ревматическими заболеваниями в период пандемии COVID-19 [90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] Продолжение таблицы 3 o n l i n e fi r s t страдающего ИВРЗ, и у каждого 100-го (0,5%) в группе контроля. Наконец совсем недавно было показано, что базовое лечение МТ ассоциируется с неадекватным синтезом анти-SARS-CoV-2 (у 62,2% пациентов) и отсутствием вирусспецифической активации CD8 + -Т-клеток [169].…”
Section: Discussionunclassified
“…Nonetheless, the risk of contracting SARS-CoV-2 and having a far worse outcome outweighs the risk of a wasted vaccine dose or the risk of a lower response rate. This common consensus led the major regulatory organizations and scientific societies worldwide to recommend the vaccination to immunocompromised patients and patients affected by rheumatologic diseases [20][21][22][23][24][25][26][27][28]. Moreover, recent research developments have underlined the importance of a third additional vaccine dose in frail patients [29].…”
Section: Sars-cov-2 Vaccinationmentioning
confidence: 99%